Physical and mechanical properties of Eucalyptus saligna wood for timber structures - Nogueira, Marta Cristina De Jesus Albuquerque; Almeida, Diego Henrique De; Araujo, Victor Almeida De; Vasconcelos, Juliano Souza; Christoforo, André Luis; Almeida, Tiago Hendrigo De; Lahr, Francisco Antonio Rocco (Associação Nacional de Tecnologia do Ambiente Construído - ANTAC, 2019)
Abstract Due to its great availability in planted forests in Brazil, Eucalyptus saligna appears as a good species to be exploited, in order to assist in the consumption of wood for construction purposes. The aim of this research was to determine the physical and mechanical properties of Eucalyptus saligna wood species for its use in civil construction. The evaluation was based on 16 physical and mechanical properties obtained according to NBR 7190 (1997) standard. Two values of moisture content were considered: 30% (above the fiber saturation point) and 12% (equilibrium moisture content) according to NBR 7190 (1997). All obtained results obtained were statistically analyzed according to the t-test at the 5% level of significance. In addition, the characteristic strength properties were also determined, for batch classification in the strength classes recommended by the Brazilian standard. Eucalyptus saligna had an apparent density of 0.58 g/cm3 and a basic density of 0.73 g/cm3. The mechanical properties, presented fc0 and fc0,k equal to 46.80 and 32 MPa, respectively. The results indicated that Eucalyptus saligna wood can be used in the construction of timber structures as structural member

Resumo A fim de auxiliar no consumo de madeira pela construção civil, o Eucalyptus saligna surge como uma boa oportunidade a ser explorada, devido à sua grande disponibilidade em florestas plantadas no Brasil. O objetivo dessa pesquisa foi determinar as principais propriedades físicas e mecânicas da madeira de Eucalyptus saligna para sua utilização na construção civil. Esta avaliação baseou-se em 16 propriedades físicas e mecânicas obtidas de acordo com a norma NBR 7190 (1997). Dois valores de teor de umidade foram considerados: 30% (acima do ponto de saturação das fibras) e 12% (teor de umidade de equilíbrio) de acordo com a NBR 7190 (1997). Todos os resultados obtidos foram analisados estatisticamente de acordo com o teste t ao nível de 5% de significância. Além disso, também foram determinadas as resistências características para classificação do lote nas classes de resistência recomendadas pela norma. O Eucalyptus saligna apresentou densidade aparente igual a 0,58 g/cm3 e densidade básica igual a 0,73 g/cm3. Em relação às propriedades mecânicas, apresentou fc0 e fc0,k iguais a 46,80 e 32 MPa, respectivamente. De acordo com os resultados, foi possível concluir que o Eucalyptus saligna pode ser utilizado na construção de estruturas de madeira como elemento estrutural.
Propriedades físicas e mecânicas da madeira de Eucalyptus saligna para estruturas de madeira
Keywords: Eucalypt; Strenght; Stiffness; Timber structures; Eucalipto; Resistência; Rigidez; Estruturas de madeira